Virtual reality in spinal cord injury rehabilitation: a systematic review of its effectiveness for balance performance and functional mobility / Amirah Mohamad, Aliff Latir and Haidzir Manaf - Mohamad, Amirah; Latir, Aliff; Manaf, Haidzir (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Post-traumatic Spinal Cord Injury (SCI) leads to poor balance performance and functional mobility, and effective rehabilitation is crucial in improving these impairments, thus improving quality of life. However, there are some barriers to effective rehabilitation, which include time-constraint, availability of therapists, and patient’s motivational level. In order to overcome these barriers, Virtual Reality (VR) was introduced in the rehabilitation setting. This review aimed to determine the effects of VR on balance performance and functional mobility in the SCI population. Four search engines were selected to search online databases, with inclusion criteria ; (i) VR as a primary intervention towards the SCI individuals and (ii) published in the English language. After screening and eligibility checks, six studies with a total of 97 participants with PEDro score (Median: 3.5) were included in this review. The results showed that the application of VR in rehabilitation is beneficial since it may induce motor relearning in retraining motor control. We proposed that dosage for the intervention of 30 to 60 minutes per session, two to five sessions per week within at least 3 weeks to 7 weeks of VR training, may have a positive impact on balance and functional mobility in the SCI population.